The use of virtual reality technologies in children with adverse health conditions: can it improve neuromotor function? a systematic review of randomized clinical trials - Silva, Ana Beatriz Januário; Barros, Waleska Maria Almeida; Silva, Robson Feliciano; Machado Silva, Beatriz; Souza, Ana Patrícia da Silva; Silva, Karollainy Gomes; Silva, José Maurício Lucas; Silva, Mayara Luclécia; Santos, Maria Eduarda Rodrigues Alves; Lopes De Souza, Sandra (Frontiers in Virtual Reality, 2025)
ObjectiveTo synthesize information on use of virtual reality (VR) technologies for improving neuromotor outcomes in children with adverse health conditions, focusing exclusively on randomized clinical trials.MethodsThe included studies followed the PICOS strategy, adhered to the methodology suggested by the PRISMA method, and complied with the protocol CRD42023416757 on the PROSPERO platform. Two databases were explored, and data collection was completed on 6 July 2024. The selected articles for this review underwent a methodological bias analysis by Joanna Briggs.ResultsA total of 824 studies were identified. After analysis using the PRISMA method and application of eligibility criteria, nine studies comprised this systematic review. Data from 260 children of both sexes were analysed across three distinct adverse health conditions: developmental coordination disorder, cerebral palsy, and autism spectrum disorder. The articles correspond to the period between 2012 and 2022. Overall, the studies reported positive outcomes regarding improvements in the neuromotor system following virtual reality-based interventions. Manual dexterity improved in two studies, while enhancements were also observed in gross and fine motor skills, balance, and trunk control.ConclusionAccording to this systematic review, motor skills may benefit from virtual reality-based interventions in children with cerebral palsy, developmental coordination disorder, and autism spectrum disorder. Domains such as manual dexterity, balance, motor coordination, and reaction time showed consistently positive outcomes.